2004
DOI: 10.1176/appi.ps.55.11.1237
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of the Effectiveness of Community-Based Mental Health Outreach Services for Older Adults

Abstract: Limited data supported the effectiveness of outreach services in identifying isolated older adults with mental illness. A more substantial evidence base indicated that home-based mental health treatment is effective in improving psychiatric symptoms. Studies are needed that apply more rigorous methods evaluating the efficacy of case identification models and subsequent treatment for older persons with a variety of psychiatric diagnoses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
44
1
3

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 60 publications
(48 citation statements)
references
References 37 publications
(59 reference statements)
0
44
1
3
Order By: Relevance
“…The benefit is even greater if the program targets individuals at risk of, suffering from, or recovering from depression [46]; incorporates clinician education [26,45,47]; and involves an enhanced role for the nurse [45,48], proactive follow-up and outcomes monitored by a care manager, enhanced IP communication, and integration between primary and specialist mental healthcare services [48-50]. These conclusions have been substantiated by systematic reviews and meta-analyses of many randomized controlled trials (RCTs) [32,45,51-53] and by consensus panels of experts who have developed evidence-based practice guidelines for the prevention, detection, and management of depression [9,26,54-56]. …”
Section: Introductionmentioning
confidence: 99%
“…The benefit is even greater if the program targets individuals at risk of, suffering from, or recovering from depression [46]; incorporates clinician education [26,45,47]; and involves an enhanced role for the nurse [45,48], proactive follow-up and outcomes monitored by a care manager, enhanced IP communication, and integration between primary and specialist mental healthcare services [48-50]. These conclusions have been substantiated by systematic reviews and meta-analyses of many randomized controlled trials (RCTs) [32,45,51-53] and by consensus panels of experts who have developed evidence-based practice guidelines for the prevention, detection, and management of depression [9,26,54-56]. …”
Section: Introductionmentioning
confidence: 99%
“…A systematic review, however, found support for the positive effects of outreach services. 522 This is clearly an area for development. There is also a paucity of comparisons of needs among older and younger persons with serious mental illnesses, and of longitudinal research investigating how needs change over time.…”
Section: Individuals In Need Of Daily Living Assistance or Social Skimentioning
confidence: 99%
“…Overall, only 10% of older adults with mental health conditions receive appropriate services (Eden, Maslow, Le, & Blazer, 2012). In contrast, the effectiveness of community-based mental health interventions for depression in older adults is supported by numerous randomized trials (Bartels et al, 2003; Bruce, Van Citters, & Bartels, 2005; Van Citters & Bartels, 2004). For example, PEARLS (the Program to Encourage Active, Rewarding Lives for Seniors) has been shown to reduce depressive symptoms and has been successfully implemented in community-based settings (Ciechanowski et al, 2004; Steinman, Cristofalo, & Snowden, 2012).…”
mentioning
confidence: 99%